Serum adenosine deaminase, catalase, and carbonic anhydrase activities in patients with renal cell carcinoma - Pirincci, Necip; Kaya, Tacettin Yekta; Kaba, Mehmet; Ozan, Tunc; Gecit, Ilhan; Ozveren, Huseyin; Ceylan, Kadir (Taylor & Francis Ltd, 2017)
Objectives: To determine whether serum levels of adenosine deaminase (AD), catalase (CAT), and carbonic anhydrase (CA) enzymes may be useful biomarkers in the diagnosis of renal tumors and may lead to early diagnosis of renal tumors. Material and methods: The study included 33 patients with renal cell carcinoma (RCC) and 31 healthy controls. The activity of serum AD, CA, and CAT was determined and analyzed using the Giusti spectrophotometric method, H2O2 substrate, and C0(2) hydration, respectively. Results: Serum AD and CA activity were significantly higher in patients with RCC than in controls. However, serum CAT activity was significantly lower in patients with RCC than in controls. Conclusion: These markers might be potentially important as an additional biochemical tool for diagnosing RCC. We believe multidisciplinary studies are needed to plan patients' preoperative and postoperative treatment and to create follow-up protocols.
Keywords: Adenosine deaminase; Antioxidant enzymes; Carbonic anhydrase; Catalase; Renal cell carcinoma